Quantification of Viral and Prokaryotic Production Rates in Benthic Ecosystems: A Methods Comparison - Rastelli, Eugenio; Dell’Anno, Antonio; Corinaldesi, Cinzia; Middelboe, Mathias; Noble, Rachel T.; Danovaro, Roberto (Frontiers in Microbiology, 2016)
Viruses profoundly influence benthic marine ecosystems by infecting and subsequently killing their prokaryotic hosts, thereby impacting the cycling of carbon and nutrients. Previously conducted studies, based on different methodologies, have provided widely differing estimates of the relevance of viruses on benthic prokaryotes. There has been no attempt so far to compare these independent approaches, including contextual comparisons among different approaches for sample manipulation (i.e., dilution or not of the sediments during incubations), between methods based on epifluorescence microscopy (EFM) or radiotracers, and between the use of different radiotracers. Therefore, it has been difficult to identify the most suitable methodologies and protocols to be used as standard approaches for the quantification of viral infections of prokaryotes. Here, we compared for the first time different methods for determining viral and prokaryotic production rates in marine sediments collected at two benthic sites, differing in depth and environmental conditions. We used a highly replicated experimental design, testing the potential biases associated to the incubation of sediments as diluted or undiluted. In parallel, we also compared EFM counts with the 3H-thymidine incubations for the determination of viral production rates, and the use of 3H-thymidine versus 3H-leucine radiotracers for the determination of prokaryotic production. We show here that, independent from sediment dilution, EFM-based values of viral production ranged from 1.4 to 4.6 × 107 viruses g-1 h-1, and were similar but overall less variable compared to those obtained by the 3H-thymidine method (0.3 to 9.0 × 107 viruses g-1h-1). In addition, the prokaryotic production rates were not affected by sediment dilution, and the use of different radiotracers provided very consistent estimates (10.3-35.1 and 9.3-34.6 ngC g-1h-1 using the 3H-thymidine or 3H-leucine method, respectively). These results indicated that viral lysis was responsible for the abatement of 55-81% of the prokaryotic heterotrophic production, corroborating previous findings of the major role of viruses in benthic deep-sea ecosystems. Moreover, our methodological comparison for the analysis of viral production in marine sediments suggests that microscopy-based approaches are simpler and more cost-effective than those based on radiotracers, also reducing time to results and overcoming issues related to radioactive waste generation.